A Review of Predatory Pricing Regulations In Digital Business In Indonesia: Islamic Law Approach - Adi Nur Rohman; Palmawati Tahir; Dwi Andayani Budisetyowati (Universiti Sains Islam Malaysia, 2026)
This study examines the need for regulating predatory pricing in Indonesia’s digital business. The rise of digital businesses, both marketplace-based and social media-based, has recently created a new phenomenon where large producers enter the market at prices significantly below the prevailing rates. This situation poses challenges, as these significantly lower prices offered by producers can threaten the sustainability of Micro, Small, and Medium Enterprises (MSMEs). Moreover, the absence of clear regulations regarding trading through social media at below-market prices could potentially lead to monopolies by large business actors. This study employs a normative juridical research method using legislative and conceptual approaches to analyse the adequacy of existing competition law in regulating predatory pricing within the digital economy. Relevant statutory instruments are examined alongside conceptual developments in predatory pricing theory to assess their applicability to digital market structures. Furthermore, this study integrates maslahah theory as a normative analytical framework to evaluate regulatory objectives in light of public interest, economic justice, and market sustainability. The findings demonstrate that regulating predatory pricing in digital markets is imperative to maintaining price stability, protecting MSMEs, and ensuring national economic resilience. More importantly, the study reveals that conventional predatory pricing standards require contextual adaptation to address the unique characteristics of digital platforms, including network effects, data-driven market power, and cross-subsidisation strategies. At the global level, this research contributes to the evolving discourse on digital competition law by offering a perspective from a developing economy with a strong MSME orientation. The integration of maslahah theory provides an alternative normative framework that complements law-and-economics approaches, offering comparative insights for policymakers and scholars seeking inclusive, ethical, and sustainable regulatory models for digital markets worldwide.